2000
DOI: 10.1074/jbc.m004006200
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Non-equivalence of the Two Isoforms of Angiotensin-converting Enzyme

Abstract: The structurally related somatic and germinal isoforms of angiotensin-converting enzyme (ACE) contain the same catalytic active center and are encoded by the same gene, whose disruption causes renal atrophy, hypotension, and male sterility. The reason for the evolutionary conservation of both isozymes is an enigma, because, in vitro, they have very similar enzymatic properties. Despite the common enzymatic properties, discrete expression of both isoforms is maintained in alternate cell types. We have previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 26 publications
1
89
1
Order By: Relevance
“…S5 A-D). In sperm from WT mice, testicular angiotensin-converting enzyme (tACE), which is responsible for fertility (22)(23)(24), was located on the outer membrane of the acrosome, whereas it was ectopically localized on the plasma membrane of sperm from Ht mice (Fig. S5 E and F).…”
Section: Resultsmentioning
confidence: 99%
“…S5 A-D). In sperm from WT mice, testicular angiotensin-converting enzyme (tACE), which is responsible for fertility (22)(23)(24), was located on the outer membrane of the acrosome, whereas it was ectopically localized on the plasma membrane of sperm from Ht mice (Fig. S5 E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Because the ACE modification involved point mutations impairing the zinc-binding properties of the N-terminal catalytic site, the tissue pattern of expression and the level of protein expression are no different from wild-type mice. This approach is different from that used by Kessler et al who created a transgenic mouse model in which rabbit testis ACE was expressed under the control of a tissue-specific promoter (Tie-1 or ␥-glutamyltransferase) in a background mouse strain that was null for the endogenous ACE gene (an ACE knock-out mouse (40)). Evaluation of ACE 7/7 mice showed that ACE enzymatic properties were consistent with our genetic design.…”
Section: Discussionmentioning
confidence: 99%
“…Male mice lacking calmegin (10,11), a testis-specific isoform of angiotensin-converting enzyme (tACE) (12,13), and ADAM2 (14) are all sterile because of the sperm defects in binding to the ZP and in migrating from the uterus into oviduct. Sperm from ADAM3-deficient mice are also defective in ZP binding but can ascend into the oviduct normally (15,16).…”
mentioning
confidence: 99%